ANALISIS PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. AMAN TOEBILAH PUTRA DI KECAMATAN MERAPI BARAT KABUPATEN LAHAT - Melia Andayani (Ekonomika, 2020)
The purpose of the study was to determine the effect of organizational culture andjob satisfaction on work performance at PT Aman Toebilah Putra, Merapi District LahatRegency. The sample in this study was 40 responden. The data were colleted throughquestionnaires and documentation. The simple linear regression analysis was carried outto test the hypotheses.Based on test result of multiple linear regression and t test shows that asignificant influence between organizational culture and job satisfaction on workperformance at PT Aman Toebilah Putra, Merapi District Lahat. And based on simulatetest show that organizational culture and job satisfaction together have a significanteffect on employee perfomance on PT. Aman Toebilah Putra in Merapi Sub-District ofDistrict Lahat.